Altered anterior insula functional connectivity in adolescent and young women with endometriosis-associated pain: Pilot resting-state fMRI study. (November 2022) - Szabo, Edina; Timmers, Inge; Borsook, David; Simons, Laura E.; Sieberg, Christine B.
Abstract: Background: Endometriosis is the leading cause of chronic pelvic pain. Alterations in brain functional connectivity have been reported in adult women with endometriosis-associated pain (EAP), however, it is still unknown if similar patterns of changes exist in adolescents. Methods : In this pilot study, resting-state fMRI scans were obtained from 11 adolescent and young women with EAP and 14 healthy female controls. Using a seed-to-voxel approach, we investigated functional connectivity between the anterior insula, medial prefrontal cortex, and the rest of the brain. Furthermore, we explored whether potential functional connectivity differences were correlated with clinical characteristics including disease duration, pain intensity, and different psychosocial factors (pain catastrophizing, fear of pain, functional disability, anxiety, and depression). Results : Our findings revealed that patients with EAP demonstrated significantly decreased connectivity between the right anterior insula and two clusters: one in the right cerebellum, and one in the left middle frontal gyrus compared to controls. Additionally, functional connectivity between the right anterior insula and the right cerebellum was positively associated with pain intensity levels. In patients with EAP, brain changes were also correlated with state anxiety and fear of pain. Conclusions: Our results are relevant not only for understanding the brain characteristics underlying EAP at a younger age, but also in enhancing future pain treatment efforts by supporting the involvement of the central nervous system in endometriosis. Highlights: Altered brain function in young patients with endometriosis-associated pain (EAP). Less functional connectivity between the right anterior insula and pain-related regions. Anterior insula and cerebellum connectivity was linked to greater pain intensity. Alterations in the pain regulatory pathways in endometriosis. Endometriosis management should include centrally mediated treatments.